STRATEGI FUNDRAISING ZAKAT INFAQ SHADAQAH DI LAZISNU DAN LAZISMU DI KABUPATEN PAMEKASAN - Iqbal Rafiqi; Maftuhatul Faizah (Assyarikah: Journal of Islamic Economic Business, 2020)
In the May-August period of 2018 the amount of LAZISNU Pamekasan Regency was very large, amounting to Rp. 979,154,185.00 while in LAZISMU Pamekasan Regency Rp. 67,624,888.00 plus in 2018 LAZISMU received the 2018 BAZNAS Award as the LAZNAS category with the best fundraising growth. That is what underlies researchers to study more deeply in the form of scientific work in the form of a thesis. This study aims to determine and describe the formulation of fundraising strategies, the implementation of fundraising strategies as well as the supporting and inhibiting factors for the implementation of Zakat Infaq Shadaqah fundraising strategies in LAZISNU and LAZISMU Pamekasan Regency. This study uses a qualitative approach to the type of descriptive research. Sources of data obtained through interviews, observation and documentation. The informants are the governing body, managers, LAZ management and fundraising staff. The findings of this study are Implementation of the fundraising strategy of zakat infaq shadaqah at LAZISNU Pamekasan Regency was carried out in collaboration with other organizations under the auspices of NU, Alfamart throughout Pemekasan, shops, NU coins, donors, rice yields, NU-Cash and through LAZISNU accounts in BRI and BMT Banks NU Mandiri. Whereas in Pamekasan Regency LAZISMU is carried out on direct withdrawal of muzakki funds, donors, coin cans, coin boxes, magazines, brochures as well as maximizing the Sang Surya BMT copling application and SMS notification service and transfer to the LAZISMU BSM account